Comparison of Multimodal Ultrasound Imaging with Conventional Ultrasound Risk Stratification Systems in Presurgical Risk Stratification of Thyroid Nodules - M Shreyamsa; Anand Mishra; Pooja Ramakant; Anit Parihar; Kul R Singh; Chanchal Rana; Sasi Mouli (Indian Journal of Endocrinology and Metabolism, 2020)
Background: Ultrasonography (US) is an indispensable tool in the management of thyroid nodules, not only for assessing tumor characteristics but also to assign risk of malignancy and guide in management. Various guidelines and US-based risk stratification systems have been proposed for this purpose. This study aims to compare the diagnostic performances of multimodal US-based risk scores (French TIRADS, TMC-RSS) with conventional US-based scoring systems (Korean TIRADS, ACR-TIRADS, ATA risk stratification). Material and Methods: A total of 168 nodules from 139 patients were studied and categorized in each of the risk stratification systems. Sensitivity, specificity, positive and negative predictive values, and accuracy of each system were computed. ROC curves were plotted and area under curve (AUC) for each scoring system noted. Results: Thirty five (21%) of the 168 nodules were malignant on final histopathological examination. TMC-RSS fared the best in predicting malignant nodules with a sensitivity of 96.2% and specificity of 88.6%, while the PPV and NPV were 97% and 86.1%, respectively. The AUC for TMC-RSS was 0.924 (95% CI, 0.860–0.988; P < 0.001). Conclusion: Multimodal US-based risk stratification incorporating non-grayscale characteristics in addition to conventional systems like the TMC-RSS improves the diagnostic performance of ultrasound imaging of thyroid nodules.